Principle Stages of Realizing Category Management in Trade Companies - K. M. Ilyenkova (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
The article identifies principle stages of the working process organization at the category management department aimed at efficient realization of the approach 'category management' and at attaining max high finance figures of the company. The author shows different points of view at the notion 'category management'. The article includes also a brief description of the essence of methodology of category management, which can help understand its basic principles and reveal during the research 6 stages of efficient realization of the approach through system organization of the working process of category management: setting goals and strategy of the company, annual planning, planning of the working process at monthly and weakly level, establishing effective interaction with relative departments, cooperation with suppliers. It was disclosed that the foundation of high-quality work of category managers is its system nature and structured work. Employees make decisions on the basis of analytical work. Their main aim is to meet needs of final customers. An important role is played by top-management that can efficiently build the company structure and provide all necessary tools to employees to reach the set goals.